A Kinetic Study of 2-Amino-4-(Methyl-Thio) Butanoic Acid By Quinaldinium Fluorochromate In Selected Hydrophilic Solvent Medium: Life Sciences-Microbiology - A. Elavarasan; J. Dharmaraja; V.Raj; B.Harikrishnan; S.Vadivel (International Journal of Life Science and Pharma Research, 2022)
A Major role in oxidation kinetics is to determine the reaction mechanism that comprise chemical reaction. In the present paper we derived rate law for reaction mechanism and to recognized the order of reaction, give rate equation, calculate the rate constant. Identify the product of this oxidation reaction.The chemical oxidation of 2-Amino-4-methyl thio-butanoic acid by Quinaldinium Fluorochromate was studied in 50-50 (v/v) selected hydrophilic solvent medium at 308 Kelvin. The reaction is acid catalysed and exhibits first order dependence with respect to oxidant, substrate, and fractional order respect to H+ ion concentrations. Chemical oxidation kinetics is the study of the rate of chemical reaction.the factors Manganesh sulphate, Acrylonitrile, Sodium perchlorate that affect these rates (or) not, and draw of ln Kobs/T verses 1/T energy diagram to find the activation energy. Addition of sodium perchlorate slightly decreases the rate of reaction. However, Acrylonitrile is not induced by the polymerization reaction, showing that there is no free radical route. Added Mn2+ increases with slightly increase rate in the reaction medium. 2-Amino-4-(MethylThio)-Butanoic acid by Quinaldinium Fluorochromate has not been reported. Hence, the investigation of oxidation of 2-Amino-4-Methyl Thio-Butanoic acid by QNFC in selected hydrophilic solvent medium and the corresponding mechanistic aspects are discussed in this research paper. A systematic kinetic work carried out to explore the physical characterization of the reactance. The characterstic effects like Substrate, Oxidant, Perchloric acid, Solvent, Sodium perchlorate, Acrylonitrile, Manganes sulphate and Influence Temperature it clearly shows effect on that reaction path. The process was carried out at four different temperatures to determine the activation conditions. The measured kinetic findings ΔH# and ΔS# are derived from the value.